2015
DOI: 10.1161/strokeaha.114.007343
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the ABC/2 Score for Intracerebral Hemorrhage

Abstract: Background and Purpose The ABC/2 score estimates intracerebral hemorrhage (ICH) volume, yet validations have been limited by small samples and inappropriate outcome measures. We determined accuracy of the ABC/2 score calculated at a specialized Reading Center (RC-ABC) or local site (site-ABC) versus the reference-standard CT-based planimetry (CTP). Methods In MISTIE-II, CLEAR-IVH and CLEAR-III trials, ICH volume was prospectively calculated by CTP, RC-ABC and site-ABC. Agreement between CTP and ABC/2 was def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…22,23 It is also wellacknowledged that ABC/2 tends to overestimate lesion volumes. 24,25 In our study, ABC/2 overestimated ICH volume by 45%, on average. While the mean SegTool measurements were .…”
Section: Discussionsupporting
confidence: 44%
“…22,23 It is also wellacknowledged that ABC/2 tends to overestimate lesion volumes. 24,25 In our study, ABC/2 overestimated ICH volume by 45%, on average. While the mean SegTool measurements were .…”
Section: Discussionsupporting
confidence: 44%
“…Because hematoma size and irregularity in shape or density are often closely correlated, the potential for increased error in larger clots is reasonable for both methods, yet based on different mechanisms. 13,15,22,32 As for the segmentation algorithm, we did not observe a reduction in accuracy associated with antithrombotic drug use. However, our random sample was not balanced regarding this variable to draw final conclusions about the accuracy of the algorithm in patients on antithrombotic drugs.…”
Section: Discussionmentioning
confidence: 64%
“…Especially, those hematomas were particularly exposed to inaccurate ABC/2 measurements, however, which implies significant volume bias within the surgical cohort. 16,[22][23][24] Regarding our hypothesis, this finding raises the possibility that inaccuracy of ABC/2 is a contributor to inconclusive results regarding surgical outcome after ICH. Moreover, it illustrates why it is of clinical interest to improve methods of ICH quantification to allow for a careful reevaluation of ICH volume as an outcome surrogate.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Fifth, hematoma volume was assessed using the ABC/2 method. Prior studies have suggested that the ABC/2 method yields hemorrhage volumes smaller than those measured using the planimetric methodology [27] and that the accuracy of this method is decreased when assessing large, irregular, or lobar hematomas [28].…”
Section: Discussionmentioning
confidence: 99%